Normal erythrocyte calpain I activity on membrane proteins under near-physiological conditions in patients with essential hypertension - Medeiros, Tereza Maria Dantas de; Ortega, Katia Coelho; Mion Júnior, Décio; Nonoyama, Kimiyo; Barretto, Orlando Cesar de Oliveira (São Paulo Medical Journal, 2002)
CONTEXT: It has been reported that the equilibrium between the erythrocyte protease calpain I and its physiological inhibitor calpastatin is disrupted in patients with essential hypertension. OBJECTIVE: To investigate the activity of non-purified calpain I in hemolysates against the erythrocytic membrane proteins, rather than against other substrates. DESIGN: Evaluation of calpain I red cell activity upon its own physiological substrates in hypertensive patients, in a near-physiological environment. SETTING: LIM-23 and LIM-40 of Hospital das Clinicas of the Faculty of Medicine of USP. SAMPLE: Patients with moderate primary hypertension over 21 years of age who were given amlodipine (n:10) and captopril (n:10) for 8 weeks, plus normal controls (n:10). MAIN MEASUREMENTS: Red cell membrane proteins were incubated with and with out protease inhibitors and with and without calcium chloride and under went polyacrylamidegelel ectrophoresis. RESULTS: Digestion of bands 2.1 and 4.1 was observed, indicating calpain I acitivity. No statistical differences regarding bands 2.1 and 4.1 were observed before treatment, between the controls and the hypertensive patients, either in ghosts prepared with out calcium or with increasing concentrations of calcium. Nor were statistical differences observed after treatment, betweenthe controls and the patients treated with amlodipine and captopril, or between the patients before and after treatment with bothdrugs. CONCLUSION: The final activity of non-purified calpain I upon its own physiological substrate, which was the approach utilized in this study,may more adequately reflect what happensin red cells. Under such conditions no imbalance favoring calpain I activity increase was observed. The protective factor provided by calpastatin against calpainI activity may diminis hunder hypertension.